2008
DOI: 10.1194/jlr.d800010-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Composition of adipose tissue and marrow fat in humans by 1H NMR at 7 Tesla

Abstract: Proton NMR spectroscopy at 7 Tesla (7T) was evaluated as a new method to quantify human fat composition noninvasively. In validation experiments, the composition of a known mixture of triolein, tristearin, and trilinolein agreed well with measurements by 1 H NMR spectroscopy. Triglycerides in calf subcutaneous tissue and tibial bone marrow were examined in 20 healthy subjects by 1 H spectroscopy. Ten well-resolved proton resonances from triglycerides were detected using stimulated echo acquisition mode sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
481
4
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(508 citation statements)
references
References 28 publications
20
481
4
3
Order By: Relevance
“…Another finding from biochemical assay is that the lipid in bone marrow is essentially all in the form of triglyceride, in agreement with a previous study [15]. The Bland-Altman plot in Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another finding from biochemical assay is that the lipid in bone marrow is essentially all in the form of triglyceride, in agreement with a previous study [15]. The Bland-Altman plot in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Panel A shows a Bland-Altman plot for the biochemical assays for triglyceride and total lipid; the very small difference between the two quantities indicates that, within error, all lipids in the samples are present as triglyceride. This finding is consistent with a previous study that reported that adipose tissue is predominantly triglyceride [15]. For the remainder of the study, the lipid and triglyceride are combined into an average Fat (%) content, defined in Methods.…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that there may be a link between the composition of fatty tissue and the risk of suffering from such diseases (11,12). The amounts of saturated, monounsaturated, and polyunsaturated fatty acids composing a lipid can be determined from a high-resolution NMR (nuclear magnetic resonance) spectrum of the sample.…”
mentioning
confidence: 99%
“…High-resolution NMR has been employed to identify the constituents of oils, animal fats, and extracts of rat adipose tissue (13)(14)(15)(16). Recently, in vivo MRS measurements of rodents (12,17,18) and humans (11) have been performed at high field strengths to calculate adipose tissue composition from the areas of the 2.1 ppm, 2.3 ppm, and 2.8 ppm (diallylic protons) proton lipid peaks. Previous studies (11,12,18) utilized the popular PRESS (point resolved spectroscopy) (19,20) pulse sequence for spatial localization.…”
mentioning
confidence: 99%
See 1 more Smart Citation